Editorial - Zeta de Pozo, Rosa (2020)
This second issue of the year of the Revista de Comunicación is published in a social context in which globally we are living in pandemic conditions, which is affecting not only the health and social field, but also the political, economic, educational, and of course that of communication. Communication has run its course in an unusual confinement environment and is experiencing an acceleration of the digital transformation process that was already developing. The data, although partial, shows us the first semester with mixed results. We notice that the coronavirus crisis has substantially increased the consumption of news in digital media and social networks, however, trust in the media is more than twice the level for social networks; the value of the media is recognized, but the cyclical downturn in the economy is hurting every publishers (Reuters, 2020). Other sectors, on the other hand, such as OTT, streaming services, video games, e-sport, data consumption, have strengthened during pandemic and have obtained beneficial results, by having their audience captive. The entertainment has the house as a permanent setting.